Working with Misspecified Regression Models - Berk, Richard (Journal of quantitative criminology, 2018)
Conventional statistical modeling in criminology assumes proper model specification. Very strong and unrebutted criticisms have existed for decades. Some respond that although the criticisms are correct, there is for observational data no alternative. In this paper, we provide an alternative.